Manajemen Penyediaan Air Minum Dan Sanitasi Berbasis Masyarakat Di Desa Toribulu Selatan Kabupaten Parigi Moutong - Nuraeni, Rini; Mangngasing, Nasir; Reza, Fachrul (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study analyzes the management of the Community-Based Water Supply and Sanitation Program (PAMSIMAS) in improving access to clean water in South Toribulu Village, , Parigi Moutong Regency, using Henri Fayol's theoretical framework, which encompasses five management functions: Planning, Organizing, Coordinating, Coordinating, and Controlling. Adopting a descriptive qualitative approach, data were collected through interviews, observations, and documentation over three months, with triangulation to ensure validity. The research location was South Toribulu Village. The results show that participatory Planning and organization are progressing well through deliberations involving the village government, KPSPAMS, and the community. However, there is still a need for strengthened routine guidance, effective coordination, and ongoing monitoring to optimize rural clean water access..